Pre- and post-economic crisis weak-form market efficiency analysis for Malaysian daily stock indices - Chin , Wen Cheong; Zaidi Isa,; Abu Hassan Shaari Mohd Nor , (Penerbit ukm, 2008)

(untitled)
In this paper, we examine the weak-form market efficiency for Malaysian sectoral stock market for the years 1996 to 2006. We focus on the random walk test under the structural change triggered by the Asian financial crisis and the drastic currency control by the Malaysian government. Our empirical results evidence a sharp contrast with the results based on the traditional unit-root test which does not take into account the effect of economic crisis. With these empirical findings, we conclude that the Malaysian stock markets are dominated by mean-reverting processes (except for Property index) under the structural change